Condylomata acuminata within perianal fistulae tracts: report of two cases. (April 2015) - Panidis, Stavros; Paramythiotis, Daniel; Papadopoulos, Vasileios N; Michalopoulos, Antonios
The commonest sights of appearance of condylomata acuminata are in the genital and anal regions. Herein we present two cases of condylomata within perianal fistulae tracts, resulting in recurrence in one case and a malignant-like tumour in the second. To our knowledge, these are the first cases reported in the literature.